ANALYSIS OF RICE CROP PRODUCTION CHANGES DUE TO LAND USE CHANGES IN BAGIK POLAK VILLAGE, LABUAPI SUBDISTRICT WEST LOMBOK REGENCY - Siddiqirly, Muhammad; Ningsi, Maulina; Mukmina, Mukmina; Putri, Mega Utami Regina; Selvia, Siska Ita (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2023)
Bagik Polak Village is located in Labuapi District, West Lombok Regency. Its area is 2.50 km2 with 7 sub-villages and a population of 4,232 people and a population density of 1,693 people/km2. Geographically, Bagik Polak is located at coordinates 8037'39" S 116007'57" E. Agricultural activities such as planting rice, corn, horticulture, and livestock, are mostly carried out by the community to meet the needs of life. However, in the last 10 years, there has been a change in the function of agricultural land to non-agricultural land. An increase in population causes this, the dynamics of development and industrial development, which require space, so it has implications for changes in land use. The purpose of this study is to analyze changes in rice crop production based on land use changes in Bagik Polak Village from 2012 to 2022. The method used in this study is the evaluative descriptive method. Data processing and analysis is carried out using ArcGis 10.8, while the stages include geometric correction, image interpretation, calculating the digitized area and field observation. The data used are Google Earth Pro satellite imagery data from 2012-2022 and rice crop production data from 2012-2022. The analysis results show that changes in the use of agricultural land into settlements and housing are the most significant changes. In 2012 the area of agricultural land was 189.51 Ha with rice production of 11.867813 quintals. However, in 2022, the area of agricultural land decreased to 168.32 Ha with rice production of 11.571725 quintals. The average rate of shrinkage of rice crop production is -0.854782108. The land conversion is the main factor causing the decline in rice crop production in Bagik Polak Village. A correlation was found between changes in agricultural land use and a decrease in rice production in Bagik Polak Village, where changes in land use were directly proportional to a decrease in rice production